Literature Review: Risk Factors For Pre Eclampsia and Anemia Among Pregnant Women in Indonesia - Liliek Pratiwi; Hutari Puji Astuti; Harnanik Nawangsari; Maharnani Tri Puspitasari (International Forum of Researchers and Lecturers, 2025)
Background: In Indonesia, the prevalence of anemia in pregnant women is 37.1%, the highest number in rural areas is 37.8%, the lowest in urban areas is 36.4%, in 2018 it increased to 48.9%. Pregnant women continue to experience the greatest rates of anemia in rural areas (49.5%) and urban areas (48.3%) (Ministry of Health of the Republic of Indonesia, 2019). In 2016, the Ministry of Health of the Republic of Indonesia reported that the three primary causes of direct maternal mortality in Indonesia during pregnancy and childbirth remain unchanged: 30.3% of the cases were connected to hemorrhage, 27.1% to hypertension during pregnancy, and 7.3% to infections.Objective: This study aims to identify risk factors for the incidence of pre-eclampsia and anemia in Indonesia.Methods: Uses the Study Literature Review method by taking data that has been published on trusted national research sites.Results: Based on research results through a review that had been carried out, researchers found 14 national studies that were included in the inclusion criteria.Conclusion: The most dominant risk factors for preeclampsia are history of preeclampsia, parity, pregnancy spacing and maternal age. Meanwhile, the most dominant risk factors for anemia in pregnant women in this study were: nutritional status, maternal age, parity and pregnancy spacing.